Efficacy and safety of levetiracetam for migraine prophylaxis in children: a systematic review and meta-analysis - Peng, Jing; Liu, Linhui; Li, Qiaoling; Liu, Maochang; Zhou, Rong; Chen, Li; Liu, Zhisheng (Frontiers in Pharmacology, 2024)
Background Levetiracetam (LEV), an antiepileptic drug, has been effective in adult migraine prevention but lacks extensive research in children. This study evaluates LEV's efficacy and safety for pediatric migraine prophylaxis.We reviewed randomized controlled trials (RCTs) and non-RCTs in major databases through January 8, 2024, focusing on four efficacy endpoints and adverse drug reactions (ADRs). Data synthesis involved pooled relative risks or odds ratios for dichotomous outcomes and mean differences for continuous outcomes, using fixed or random effects models as appropriate.Eight studies with 190 participants showed that after taking LEV, the mean headache frequency decreased 5.19 per month (MD: -5.19, 95% CI: -7.11 to -3.27, P<0.00001) and improved headache-free rates to 28% (95% CI: 0.17 to 0.41). Over 83% experienced a >50% reduction in monthly headache frequency. The migraine disability score decreased by 33.51 points (MD: -33.51, 95% CI: -38.46 to -28.55, P<0.00001). ADR incidence did not significantly differ between LEV and control groups (RR: 1.06, 95% CI: 0.39 to 2.85, P=0.91), with an overall ADR rate of 18% (95% CI: 0.13 to 0.24).The most common ADR was irritability (12%), leading to treatment discontinuation in 13% of cases (95% CI: 0.05 to 0.30).Conclusions LEV has shown good efficacy in preventing pediatric migraines. However, its safety requires further confirmation through more extensive and well-designed RCTs.